Associations among scaffold presentation, reward mechanisms and problem-solving behaviors in game play. (April 2018) - Sun, Chuen-Tsai; Chen, Li-Xian; Chu, Hsiu-Mei
Abstract: Learning assistance tools used with digital games—commonly called scaffolds —can reduce player frustration and help them create problem-solving strategies while supporting achievement. Reward mechanisms in the form of external incentives are also believed to enhance motivation and promote learning, but possibly at the expense of excessive learner reliance. Some researchers have suggested that reward mechanisms can be used to discourage players from becoming dependent on scaffolds. For this study we customized Professor Sudoku, a simplified version of the popular digital reasoning game, to investigate the effects of scaffold presentation-plus-reward mechanism on problem-solving behaviors and actions aimed at leveling-up. A total of 126 participants were divided into active scaffold (providing direct assistance to players at the beginning of a game), passive scaffold (provided by the game system when players made three mistakes within a specified time frame), and hidden scaffold groups (accessible at any time). Each scaffold served three functions: critical feature marking, frustration control, and demonstration. The three groups were given point-gain and point-loss reward mechanisms. Our data indicate that the appropriate presentation of one or more scaffolds reduced player reliance on support, thereby increasing the potential for positive learning effects and reducing frustration. Results suggest that the reward mechanism promoted independent problem solving instead of reliance on scaffolds, and that the addition of scaffolds and reward mechanisms encouraged experienced players to create new rules, overcome the limitations of existing rules, and develop more complex learning strategies. We discuss the need to carefully design scaffold presentation type according to specific instructional purposes, and possible benefits for teachers in terms of analyzing the difficulties that individual students face when solving numerical problems. Highlights: We study how a group of Taiwanese primary students solve Professor Sudoku problems. Game scaffolds provided more flexibility than learning scaffolds. Restricted scaffolds and simple rewards promoted autonomous and active learning. Proper phasing out of scaffolds enhanced learning effects and reduced frustration. Hidden scaffolds encouraged learners to try new problem-solving strategies.